Bacterial Meningitis in Children in a Tertiary Care Hospital in South Punjab: A Retrospective Analysis of Clinical and Laboratory Features (Journal of Fatima Jinnah Medical University, 2018)
Background: In children, meningitis is still in the ten common causes of death in many countries. Bacterial meningitis has high incidence of mortality in childhood. Both clinical evaluation and the use of laboratory investigations are important tools in finding cause of bacterial meningitis .Objective: The purpose of the research is to study the demographic features, yield of gram staining, the incidence and etiology of bacterial meningitis in children of ≥ 2 months to ≤14 years during a 1 year period, from October 2013 to September 2014, in Department of Pediatrics, Nishtar Hospital Multan & in Pathology Department Nishtar Medical College Multan.Methods: Diagnosis of bacterial meningitis was mainly based on criteria published by the World Health Organization (WHO) .Children having history of intake of antibiotic in the last 5 days which can cross the blood brain barrier and children with tuberculosis meningitis were excluded. The patients were evaluated according to their sex, age, clinical features and pathogenic microorganisms. Patients were divided in three age groups. CSF was collected by lumbar puncture in ward and biochemistry, microscopy , gram staining and bacteriological culture was performed in pathology department .Statistical analysis of data was done by using Microsoft Excel, and SPSS 16.Results: A total of 130 patients (2.53% of the total admissions) were included in the study. Male patients were 76(58.5%) and 54 (41.5%) patients were female. Out of 130, 54(41.5%) patients were in the age group of ≥2 months-1 year, 40(30.8%) in the group of 1-5 years and 36(27.7%) in group of 5-14 years. 72.3% children were below 5 years in our study . Gram staining was positive in 74(56.9%) cases and negative in 56(43.1%). The most common clinical symptoms was fever and headache and the least was vomiting .The CSF cultures were positive in 60(46.2%) cases and negative in 70(53.8%).The three most common pathogens reported are Streptococcuspneumonia 26 (20%),Neisseriaemeningitidis 20 (15.4%) and Hemophilusinfluenzae b , 12 (9.2%).Conclusion: Bacterial meningitis is still a very common serious infection in children below 5 years .The most common pathogen involved in the etiology of bacterial meningitis was Streptococcus pneumoniae. The yield of gram staining and culture though comparable with the national studies but lower than reported internationally.
Keywords: Children; Bacterial Meningitis